Implementation of Environmentally Friendly Monitoring Method: "Green Watch" and "Image Analysis" in Sustainable Resource Utilization in the Coast Community of the Gulf of Amurang, North Sulawesi - Kaligis, Fontje Georis Judri; Ompi, Medy (Jurnal Ilmiah PLATAX, 2016)
Monitoring the condition of coral reefs using 'green watch' and 'image analysis' in the use of sustainable resource in the coastal communities of the Gulf of Amurang North Sulawesi has been conducted with the purpose of (1) to understand the condition of coral reefs in the waters of TEEP and Kapitu, (2) the coastal communities can utilize the method of 'green watch' and 'image analysis', and also can do the monitoring themselves both groups and individuals. Results of research by two methods illustrates that there are seven types of coral growth in the waters of Teep, and 8 types in the waters Kapitu village, where each type of coral growth showed different in percent cover. Overall reef condition for waters in the village of TEEP is very good with 79% of live coral, while the Kapitu village is good with a percentage of live coral is 64%. With this condition is expected that the community can do the monitoring continuously, and also rehabilitate the damage corals. By doing so the resources will be always available for both village. Keywords: Coral Reef, associate organisms, 'green watch', 'image analysis', live coral and dead coral, percent cover, Abstrak Monitoring kondisi terumbu karang dengan menggunakan metode ‘green watch’ dan ‘ image analysis’ dalam pemanfaatan sumberdaya yang berkelanjutan di komunitas pesisir Teluk Amurang Sulawesi Utara telah dilakukan dengan tujuan (1) memahami kondisi terumbu karang di perairan Teep dan Kapitu, (2) masyarakat nelayan dapat memanfaatkan metode ‘green watch’ dan ‘image analysis’, sekaligus melakukan monitoring secara mandiri baik kelompok maupun individu. Hasil penelitian dengan dua metode ini menggambarkan bahwa ada 7 tipe pertumbuhan karang di desa Teep, dan 8 tipe di perairan desa Kapitu, di mana masing masing tipe pertumbuhan karang hadir dengan presentase tutupan yang berbeda. Kondisi karang secara keseluruhan untuk perairan di Desa Teep adalah yang sangat bagus dengan 79 % karang hidup, sedang untuk desa Kapitu adalah cukup bagus dengan presentase karang hidup adalah 64 %. Dengan kondisi ini diharapkan masyarakat dapat mempertahankan, dengan cara melakukan kegiatan monitoring secara berkesinambungan, sekaligus merehabilitasi kondisi karang yang telah rusak. Dengan mempertahankan kondisi yang baik ini maka servis dari ekosistem ini terhadap masyarakat di kedua Desa ini akan terus ada. Kata kunci: Terumbu Karang, organisme asosiasi, ‘green watch’, ‘image analysis’, karang hidup, karang mati, persentase tutupan.